(untitled) (Revista Electrónica REDINE, 2018)
The article aims to propose a series of didactic resources from the constructivism for the teaching of general geography, directed to professors of the Department of Social Sciences-IPB, with the purpose of improving the teaching practice through the design of didactic resources validated by experts. This research is framed in the constructivism of Bruner, where the teacher handles the contents and consequently their learning becomes more significant. The nature of the research is positivist and of quantitative type, being a special project, with non-experimental design, developed in three phases; Diagnosis, design of didactic resources and validation of the proposal, in a population of 9 teachers. It is concluded that because of the lack of didactic resources the proposal is very useful and pertinent, because it is assertive to nurture new materials to teachers and in itself, to improve the teaching process of geography.